Affective pictures processing is reflected by an increased long-distance EEG connectivity - Güntekin, Bahar; Femir, Banu; Turp Gölbaşı, Bilge; Tülay, Elif; BAŞAR, EROL (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2017)
Analysis of affective picture processing by means of EEG has invaded the literature. The methodology of event-related EEG coherence is one of the essential methods used to analyze functional connectivity. The aims of the present study are to find out the long range EEG connectivity changes in perception of different affective pictures and analyze gender differences in these long range connected networks. EEGs of 28 healthy subjects (14 female) were recorded at 32 locations. The participants passively viewed emotional pictures (IAPS, unpleasant, pleasant, neutral). The long-distance intra-hemispheric event-related coherence was analyzed for delta (1-3.5 Hz), theta (4-7.5 Hz), and alpha (8-13 Hz) frequency ranges for F-3-T-7, F-4-T-8, F-3-TP7, F-4-TP8, F-3-P-3, F-4-P-4, F-3-O-1, F-4-O-2, C-3-O-1, C-4-O-2 electrode pairs. Unpleasant pictures elicited significantly higher delta coherence values than neutral pictures (p < 0.05), over fronto-parietal, fronto-occipital, and centro-occipital electrode pairs. Furthermore, unpleasant pictures elicited higher theta coherence values than pleasant (p < 0.05) and neutral pictures (p < 0.05). The present study showed that female subjects had higher delta (p < 0.05) and theta (p < 0.05) coherence values than male subjects. This difference was observed more for emotional pictures than for neutral pictures. This study showed that the brain connectivity was higher during emotional pictures than neutral pictures. Females had higher connectivity between different parts of the brain than males during emotional processes. According to these results, we may comment that increased valence and arousal caused increased brain activity. It seems that not just single sources but functional networks were also activated during perception of emotional pictures.
Keywords: EEG; Event related coherence; EEG connectivity; Emotion; IAPS; Gender; Event-Related Synchronization; Parkinsons-Disease Patients; Functional Connectivity; Brain Oscillations; Electroencephalograph Asymmetry; Dysfunctional Anger; Facial Expressions; Emotional Arousal; Evoked Emotions; Visual-Stimuli